2021
DOI: 10.1101/2021.01.06.20248743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-Analysis of Adenoviral p53 Gene Therapy Clinical Trials in Recurrent Head and Neck Squamous Cell Carcinoma

Abstract: BackgroundWe conducted a meta-analysis of previous adenoviral p53 (Ad-p53) treatment data in recurrent head and neck squamous cell carcinoma (HNSCC) patients to identify optimal Ad-p53 treatment methods for future clinical trials.MethodsThe meta-analysis involved recurrent HNSCC patients treated with Ad-p53 for whom p53 genotyping and immunohistochemistry tumor biomarker studies had been performed (n = 70). Ad-p53 tumor treatment responses defined by RECIST 1.1 criteria were correlated with Ad-p53 dose and tum… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…On the other hand, however, many of those tumours accumulate excessive mutp53 protein, which may act in a dominant-negative manner to neutralize the reintroduced wtp53. Interestingly, a meta-analysis of patients with recurrent HNSCC treated with adenovirus–p53 gene therapy showed that all responders had only weak p53 staining by immunohistochemistry (IHC) and no TP53 missense mutations 178 . Hence, abundant mutp53 might indeed restrict the efficacy of wtp53 gene therapy, suggesting strong p53 IHC staining as an exclusion criterion for such treatments.…”
Section: P53-based Genetic Therapiesmentioning
confidence: 99%
“…On the other hand, however, many of those tumours accumulate excessive mutp53 protein, which may act in a dominant-negative manner to neutralize the reintroduced wtp53. Interestingly, a meta-analysis of patients with recurrent HNSCC treated with adenovirus–p53 gene therapy showed that all responders had only weak p53 staining by immunohistochemistry (IHC) and no TP53 missense mutations 178 . Hence, abundant mutp53 might indeed restrict the efficacy of wtp53 gene therapy, suggesting strong p53 IHC staining as an exclusion criterion for such treatments.…”
Section: P53-based Genetic Therapiesmentioning
confidence: 99%